A Lightweight Blockchain-based Public-Key Authenticated Encryption with Multi-Keyword Search for Cloud Computing. (15th October 2022) - Du, Haorui; Chen, Jianhua; Lin, Fei; Peng, Cong; He, Debiao
Abstract : Cloud computing can provide users with sufficient computing resources, storage, and bandwidth to meet their needs. Data security and privacy protection are among the new threats faced by users. Searchable encryption is the combination of search technology and encryption technology. Searchable encryption can upload the user's data to the cloud server after special encryption, and can realize the function of retrieving according to keywords. Comparatively to symmetric searchable encryption (SSE), public key searchable encryption (PEKS) simplifies key management greatly. However, most existing public key authenticated encryption with keyword search (PAEKS) schemes are based bilinear pairing, making them computationally expensive. Apart from this, complex retrieval requirements and the integrity of the results had not been considered. To address these problems, we propose a blockchain-based PAEKS schemes supporting multi-keyword queries and integrity verification. In addition, we provide security proofs for the PAEKS scheme under the decisional oracle Diffie-Hellman (DODH) assumption. This scheme a scheme that requires less storage and computational power than other schemes of the same kind.